Penentuan Perlakuan Optimal Substitusi Tepung Ampas Kelapa terhadap Mutu Sensorik dan Kimia Brownies Kukus - Rio Ilsar Fitransyah; Saragih, Dewi Sartika; Yunita Cucikodana; Muhammad Deddy Syafrullah; Maulina Azkiya Mazdalifah; Depia Swari; Dinda Sofie Y Aurora (Jurnal Sains dan Teknologi Pangan, 2025)
This study aimed to evaluate the utilization of coconut pulp waste as a partial substitute for wheat flour in steamed brownies to determine the optimal formulation based on consumer acceptance and chemical composition. Coconut pulp is abundant in Indonesia and has high nutritional potential, particularly in fiber, protein, and fat content. The research was conducted in three stages: preparation of steamed brownies with various substitution levels of coconut pulp (0%, 15%, 30%, 45%, and 60%), sensory evaluation using a hedonic rating test, and product characterization including proximate and dietary fiber analyses. The sensory evaluation revealed that the 15% substitution level achieved the highest acceptance scores for taste, aroma, color, and texture, with mean values ranging from 4.46 to 4.97 on a five-point hedonic scale, categorized as “liked.” Proximate analysis of selected formulations (0–30%) showed that increasing coconut pulp levels enhanced the protein content from 10.33% to 19.43%, while reducing fat content from 9.44% to 5.72% and carbohydrate content from 46.59% to 39.95%. It can be concluded that 15% coconut pulp substitution produced the most acceptable steamed brownies in terms of sensory quality, while higher substitution levels improved nutritional value, particularly protein and fiber contents, making it a potential functional food alternative based on local resources.